The Relationship between Situational Leadership and School Culture on Elementary School Teachers’ Work Discipline - Malia, Ikri; Azmi, Fachruddin; Hadijaya, Yusuf (Jurnal Basicedu, 2023)
Teachers' awareness of work discipline is still relatively poor in schools. This study aims to determine the relationship between situational leadership and school culture with the work discipline of teachers at SDIT Al-Hijrah 2 Deli Serdang. This study uses a quantitative approach. Data were collected by means of a questionnaire involving 42 respondents, then analyzed by statistical analysis of multiple correlations, with the help of SPSS version 17.0. The results of the research and analysis of statistical data show that, partially, the situational leadership variable has an effect of 0.582, which means that there is a moderate relationship between the situational leadership variable and teacher work discipline, namely 58.2%. Furthermore, the school culture variable has an effect of 0.771, which means that 77.1% has a strong relationship between the school culture variable and the teacher's work discipline. Simultaneously, the relationship given by the school principal and school culture variables to teacher work discipline is 0.610%, which is 61%, while 39% (100% -61%) is again influenced by other variables. On this basis, it can be concluded that situational leadership and school culture have a strong relationship with the work discipline of elementary school level teachers.